Development of Belarus's Foreign Economic Ties in the Context of CIS Integration Processes. Issue 6 (2nd June 2016) - Shuburovich, A.V.
Abstract : This article examines the main trends in the development of Belarus's foreign economic ties since 2000. We analyze the dynamics and structure of Belarus's foreign trade, its distribution across the country's major trading partners, and the country's migration ties, including labor migration. We show that Russia is undoubtedly Belarus's main foreign economic partner in all major areas.